Tuberculose pulmonar e o uso de drogas ilícitas : entre a cura e o abandono - Cassiano, Janete Galvão Martins (2014)
Tuberculosis is an infectious and contagious disease caused by a bacterium, Mycobacterium tuberculosis. Treatment Refusal for pulmonary tuberculosis in patients with smear-positive favors the maintenance of the transmission chain, as well as increased resistance to first-line chemotherapy. Starting treatment, give it up, portray, leave again… situation increasingly common in the population affected by tuberculosis and uses drugs, licit or illicit. The consumption of psychoactive substances has increased since the second half of the twentieth century, becoming a mass phenomenon in recent decades and a public health problem. According to WHO, about 10% of the populations of urban centers world consume abusively psychoactive substances, regardless of age, sex, education level and purchasing power. This study aims to evaluate the influence of the abusive use of illegal drugs in the abandonment of treatment for pulmonary tuberculosis in a Unit of Primary Health Care in Fortaleza. Through a epidemiologic, observational and retrospective study, socio-demographic factors and clinical factors were analyzed in patients treated for pulmonary tuberculosis, verifying the presence of substance abuse in this population, and the influence of these in abandonment of treatment, using structured questionnaires (general questionnaire and ASSIST). Results: of the 116 TB cases investigated, 68.9% are male, with a mean age of 37.5 years, mulatto (72.4%), single (56.9%), with incomplete primary education (50%). The employment status of the majority (37%) were unemployed. As to the epidemiological profile of the case, 84.4% were new cases, 13% of return after default and 2.6% of recurrence. The cause of the closure of the case was by treatment refusal in 36% of patients. Comparing the differences between the group cure and abandonment, there was no significant difference between the mean ages of the two groups (p> 0.75). In both groups there was a predominance of males, but had a significantly greater difference in the dropout (p = 0.0001). In the group abandoned, the education level was lower than the cure group (p = 0.017). There was an association between dropout and unemployment (p <0.0001) and return after default. The ASSIST questionnaire showed that the frequency of drug use in life corresponded to 95.1% for alcohol, followed by tobacco. (51.6%). Cannabis sativa, cocaine and crack were cited by 41.9% of respondents. Inhalants like lolo and glue had already been tried by 19.3%. The use of crack needs intensive treatment in the majority of users (61.9%), demonstrating the chemical addiction to this substance. Conclusion: The abandonment of tuberculosis treatment shows a significant risk in patients using drugs, especially illicit substances with abuse use, necessitating the intervention, whether a brief intervention or more intensive treatment.